Effects of nano-SiO2 on sulfate attack resistance of multi-solid waste-based alkali-activated mortar - Jingjun Li; Shichao Wu; Yuxuan Shi; Yongbo Huang; Ying Tian; Duinkherjav Yagaanbuyant (Case Studies in Construction Materials)
This study investigated the performance of multi-solid waste-based alkali-activated mortar (MAAM) subjected to wet-dry cycling and sulfate exposure. The effects of nano-SiO2 (NS) modification, both before and after exposure, on the material's mechanical properties and sulfate attack resistance were evaluated through various indices, including flexural strength, corrosion resistance coefficient, mass loss rate, and SO42- concentration. Additionally, a cumulative damage model was developed to assess the overall degradation. The mechanism behind the improved sulfate attack resistance due to nano-modification was elucidated using advanced microscopic techniques, such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and backscattered electron imaging (BSE). The study demonstrated that both flexural and compressive strengths initially increased and then decreased with rising NS content. The highest strength values were observed at 2 % NS content (NS2.0), with flexural and compressive strengths enhanced by 27.4 % and 22.8 %, respectively, compared to the undoped group (NS0). After sulfate attack, the NS2.0 group exhibited superior flexural strength, a more stable corrosion resistance coefficient, and lower mass loss, damage rate, and SO42- concentration compared to the NS0 group. In addition, both groups followed similar trends with increasing wet-dry cycling. Microstructural analysis further revealed that NS-modified specimens possessed a denser and more uniform microstructure than the unmodified ones, underscoring the critical role of NS in improving resistance to sulfate attack in the MAAM.